The Mediating Role of Click-Through Rate in Emotional Appeal Copywriting and ROAS Performance: Evidence from a Crowdfunding Platform - Muhammad Haikal ‘Alim; Fajar Nugraha (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study investigates the effectiveness of emotional appeal dimensions in digital copywriting, specifically the Identifiable Victim effect, Narrative Structure, and Transformational Diction, on the financial performance (Return on Ad Spend/ROAS) of digital campaigns on the Indonesian crowdfunding platform Raihmimpi.id. Addressing the challenges of the modern attention economy and content clutter, this research examines the mediating role of Click-Through Rate (CTR) using a quantitative panel data approach comprising 490 observations from 49 active advertisements. Data were analyzed using Hayes' PROCESS Macro v4.2 with 5,000 bootstrapping iterations. The empirical findings reveal that the Identifiable Victim effect successfully drives initial audience engagement and fully mediates ROAS, confirming the efficiency of visual-centric peripheral cues. Conversely, traditional Narrative Structure fails to significantly impact either CTR or ROAS, highlighting the detrimental effects of high cognitive load and ad avoidance in fast-paced digital environments. Intriguingly, Transformational Diction fails to generate clicks, likely due to the activation of consumers' Persuasion Knowledge and skepticism, yet it maintains a significant direct effect on ROAS. This anomaly suggests a behavioral bypass where emotionally charged language influences financial contributions through subconscious affective priming, circumventing mechanical engagement metrics. The study extends the application of the Elaboration Likelihood Model and Persuasion Knowledge Model to digital philanthropy, providing actionable managerial strategies for optimizing advertising cost efficiency.